Natural Progression of Atherosclerosis from Pathologic Intimal Thickening to Late Fibroatheroma in Human Coronary Arteries: A Pathology Study - Otsuka, Fumiyuki (Atherosclerosis, 2015)
OBJECTIVE: Smooth muscle cells, macrophage infiltration and accumulation of lipids, proteoglycans, collagen matrix and calcification play a central role in atherosclerosis. The early histologic changes of plaque progression from pathologic intimal thickenings (PIT) to late fibroatheroma lesions have not been fully characterized. METHODS: A total of 151 atherosclerotic coronary lesions were collected from 67 sudden death victims. Atherosclerotic plaques were classified as PIT without macrophage infiltration, PIT with macrophages, and early and late fibroatheromas. Presence of macrophages and proteoglycans (versican, decorin and biglycan) were recognized by specific antibodies while hyaluronan was detected by affinity histochemistry. Lipid deposition was identified by oil-red-O, and calcification was assessed following von Kossa and alizarin red staining. RESULTS: Lesion progression from PIT to late fibroatheroma was associated with increase in macrophage accumulation (p<0.001) and decreasing apoptotic body clearance by macrophages (ratio of engulfed-to-total apoptotic bodies) (p<0.001). Lipid deposition in lipid pool of PIT had a microvesicular appearance whereas those in the necrotic core were globular in nature. Overall, the accumulation of hyaluronan (p<0.001), and proteoglycan versican (p<0.001) and biglycan (p=0.013) declined along with lesion progression from PIT to fibroatheromas. Microcalcification was first observed only within areas of lipid pools and its presence and size increased in lesions with necrotic core. CONCLUSIONS: PIT to fibroatheroma lesions are accompanied by early lipid accumulation, followed by macrophage infiltration with defective clearance of apoptotic bodies along with decrease in proteoglycan and hyaluronan in lipid pools that convert to necrotic cores. Calcification starts in PIT and increases with plaque progression.